Insights into the defensive roles of lncRNAs during Mycoplasma pneumoniae infection - Yang, Zhujun; Zhou, Junjun; Su, Nana; Zhang, Zifan; Chen, Jiaxin; Liu, Peng; Ling, Peng (Frontiers in Microbiology, 2024)
Mycoplasma pneumoniae causes respiratory tract infections, affecting both children and adults, with varying degrees of severity ranging from mild to life-threatening. In recent years, a new class of regulatory RNAs called long non-coding RNAs (lncRNAs) has been discovered to play crucial roles in regulating gene expression in the host. Research on lncRNAs has greatly expanded our understanding of cellular functions involving RNAs, and it has significantly increased the range of functions of lncRNAs. In lung cancer, transcripts associated with lncRNAs have been identified as regulators of airway and lung inflammation in a process involving protein complexes. An excessive immune response and antibacterial immunity are closely linked to the pathogenesis of M. pneumoniae. The relationship between lncRNAs and M. pneumoniae infection largely involves lncRNAs that participate in antibacterial immunity. This comprehensive review aimed to examine the dysregulation of lncRNAs during M. pneumoniae infection, highlighting the latest advancements in our understanding of the biological functions and molecular mechanisms of lncRNAs in the context of M. pneumoniae infection and indicating avenues for investigating lncRNAs-related therapeutic targets.